Corporate Sukuk vs. Bonds in Indonesia’s Dual Financial System: 2010–2024 - Irvan Yulian Noor; Permata Wulandari (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Indonesia, a leading global sukuk issuer, sees only 25.6% of corporate debt issuances as sukuk from 2010 to 2024, indicating barriers to adoption despite its dual financial system supporting both Islamic and conventional instruments. This study investigates why Indonesian corporations prefer sukuk over conventional bonds for long-term financing. It aims to identify key determinants influencing this choice within the dual financial framework, integrating conventional capital structure theories with Islamic finance principles. Employing a two-stage binary logistic regression on 1,095 debt issuances from the Indonesia Stock Exchange, the study examines issuance-specific, firm-specific, ownership, and external factors. Findings reveal that lower credit ratings, higher leverage, and significant government or institutional ownership increase sukuk issuance likelihood, with a notable surge during the COVID-19 pandemic. These results align with agency and pecking order theories, suggesting sukuk serves strategic purposes beyond Sharia compliance. The study concludes that sukuk adoption reflects financial constraints and ethical alignment, offering practical implications for regulators to enhance market competitiveness through improved liquidity and incentives, and for corporate managers to leverage sukuk for accessing Sharia-compliant capital, particularly for firms with specific financial and ownership profiles.